Development of electronic rubric to assess improvement of employability skills student. Issue 4 (March 2021) - Subekti, S; Ana, A; Muktiarni, M
Abstract: This research is carried out on the basis of the need for assessment tools to assess employability skills. Assessment which made refer to the applicable competency standard and adjusted to the needs of each proficiency field. The urgency of this research is to design an electronic rubric evaluation tool for educators. This study aims to develop electronic rubric in measuring employability skills due to the condition which not every skills assessment uses standard assessment tools, it encourages researcher to develop assessment tools that can be used as the process of measuring employability skills by work based learning. The research method that used is Design Based Research to develop prototypes of performance evaluation tool or performance assessment. The design of performance assessment in this research is web based using SmartRubric platform. The SmartRubric application uses browser technology and is accessed through a computer network. Besides using a computer or laptop system on this application is also using mobile, such as mobile phones, smartphone, tablet PC, Mac, Android, BB and others, as long as the device has a browser application for internet access. The SmartRubric application has a program that is stored on the Server and sent via the internet and accessed through a browser interface, so that it can be accessed using a web browser through an internet network or intranet. The use of SmartRubric application through computer software that is coded in a programming which supports web-based software namely HTML, JavaScript, CSS, Ruby, Python, Php, Java and any other programming.